Finds the analytical form of the row sum of the inverse of a tridiagonal matrix.
$begingroup$
Let $bf A$ be an $N times N$ tri-diagonal matrix $mathbf{A}=frac{1}{{N + 1}}left( {begin{array}{*{20}{c}}
{ - 2}&1&{}&{}\
1&{ - 2}& ddots &{}\
{}& ddots & ddots &1\
{}&{}&1&{ - 2}
end{array}} right)$. How do we find a analytical form of row sum of its inverse $mathbf{A}^{-1}$. Let $s(i)$ denote the sum of elements of the $i$th row in $mathbf{A}^{-1}$, then $s(i)=sum_{j=1}^Nmathbf{A}^{-1}(i,j)$.
linear-algebra
$endgroup$
add a comment |
$begingroup$
Let $bf A$ be an $N times N$ tri-diagonal matrix $mathbf{A}=frac{1}{{N + 1}}left( {begin{array}{*{20}{c}}
{ - 2}&1&{}&{}\
1&{ - 2}& ddots &{}\
{}& ddots & ddots &1\
{}&{}&1&{ - 2}
end{array}} right)$. How do we find a analytical form of row sum of its inverse $mathbf{A}^{-1}$. Let $s(i)$ denote the sum of elements of the $i$th row in $mathbf{A}^{-1}$, then $s(i)=sum_{j=1}^Nmathbf{A}^{-1}(i,j)$.
linear-algebra
$endgroup$
add a comment |
$begingroup$
Let $bf A$ be an $N times N$ tri-diagonal matrix $mathbf{A}=frac{1}{{N + 1}}left( {begin{array}{*{20}{c}}
{ - 2}&1&{}&{}\
1&{ - 2}& ddots &{}\
{}& ddots & ddots &1\
{}&{}&1&{ - 2}
end{array}} right)$. How do we find a analytical form of row sum of its inverse $mathbf{A}^{-1}$. Let $s(i)$ denote the sum of elements of the $i$th row in $mathbf{A}^{-1}$, then $s(i)=sum_{j=1}^Nmathbf{A}^{-1}(i,j)$.
linear-algebra
$endgroup$
Let $bf A$ be an $N times N$ tri-diagonal matrix $mathbf{A}=frac{1}{{N + 1}}left( {begin{array}{*{20}{c}}
{ - 2}&1&{}&{}\
1&{ - 2}& ddots &{}\
{}& ddots & ddots &1\
{}&{}&1&{ - 2}
end{array}} right)$. How do we find a analytical form of row sum of its inverse $mathbf{A}^{-1}$. Let $s(i)$ denote the sum of elements of the $i$th row in $mathbf{A}^{-1}$, then $s(i)=sum_{j=1}^Nmathbf{A}^{-1}(i,j)$.
linear-algebra
linear-algebra
asked Dec 4 '18 at 8:14
TuyetTuyet
477210
477210
add a comment |
add a comment |
2 Answers
2
active
oldest
votes
$begingroup$
Let $s = (s_i)$ be the $Ntimes 1$ matrix of row sums. i.e. the entry at $i^{th}$ row is $s_i = s(i)$.
Let $u$ be the $Ntimes 1$ matrix with all entries $1$. By definition of the row sums, we have
$$s = A^{-1} u quadiffquad As = u$$
Express everyting in terms of entries of $A$ and $s$, this is equivalent to following set of equations:
$$begin{array}{rrrrrrl}
- 2 s_1& + s_2&&&& = N+1\
s_1 & -2s_2& + s_3 &&& = N+1\
&& ddots & ddots & +s_{N} &= N+1\
&&&s_{N-1}&{ -2s_{N}} &= N+1
end{array}tag{*1}$$
Introduce two dummy variables $s_0 = s_{N+1} = 0$. This can be summarized as
$$s_{k-1} - 2s_{k} + s_{k+1} = N+1quadtext{ for } k = 1,ldots, N$$
Notice what's on the left has the form of second order finite difference. To get a constant
on the right. $s_k$ need to be a quadratic polynomial in $k$.
Since $s_0 = s_{N+1} = 0$, we have $s_{k} = alpha k (k - N - 1)$ for some constant $alpha$. One can fix $a$ using any equation in $(*1)$. At the end, we find $alpha = frac{N+1}{2}$ and
$$s(k) = s_k = frac{N+1}{2}k(k - N - 1)$$
$endgroup$
add a comment |
$begingroup$
The elements of the inverse are
$$
[A^{-1}]_{ij} = (N + 1) begin{cases}
(-1)^{i + j} theta_{i - 1}phi_{j + 1}/theta_N & i < j \
theta_{i - 1}phi_{j + 1}/theta_N & i = j tag{1} \
(-1)^{i + j} theta_{j - 1}phi_{i + 1}/theta_N & i > j \
end{cases}
$$
where $theta$ satisfy the recurrence relation
$$
theta_i = -2theta_{i - 1} - theta_{i - 2}
$$
with initial condition $theta_0 = 1$, $theta_1 = -2$ this leads to
$$
theta_i = (-1)^{i}(i + 1) tag{2}
$$
Similarly
$$
phi_i = -2phi_{i + 1} - phi_{i + 2}
$$
with conditions $phi_{N + 1} = 1$, $phi_N = -2$:
$$
phi_{i} = (-1)^{1 + i - N}(2 - i + N) tag{3}
$$
Replacing in $(1)$, you get
begin{eqnarray}
[A^{-1}]_{ij} &=& (N + 1) begin{cases}
(-1)^{i + j} (-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i < j \
(-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i = j \
(-1)^{i + j} (-1)^{j - 1}j(-1)^{2 + i - N}(1 - i + N)/(-1)^N(N + 1) & i > j \
end{cases} \ &=&
-begin{cases}
i(1 - j + N) & i < j \
i(1 - j + N) & i = j tag{4}\
j(1 - i + N) & i > j \
end{cases}
end{eqnarray}
Now it is a matter of adding these components
$$bbox[5px,border:2px solid blue]
{
s_i = sum_{j = 1}^N [A^{-1}]_{ij} = begin{cases}
N(N - 7)(N + 1)/2 & 1 leq N leq 8 \
4(N^2 - 6N - 7) & text{otherwise}
end{cases}
}
$$
$endgroup$
$begingroup$
$N = 1, 8$ isn't a special case; the formula for $1<N<8$ still applies.
$endgroup$
– Display name
Dec 4 '18 at 9:35
$begingroup$
@Displayname Thanks for the suggestion. Already fixed it
$endgroup$
– caverac
Dec 4 '18 at 9:37
add a comment |
Your Answer
StackExchange.ifUsing("editor", function () {
return StackExchange.using("mathjaxEditing", function () {
StackExchange.MarkdownEditor.creationCallbacks.add(function (editor, postfix) {
StackExchange.mathjaxEditing.prepareWmdForMathJax(editor, postfix, [["$", "$"], ["\\(","\\)"]]);
});
});
}, "mathjax-editing");
StackExchange.ready(function() {
var channelOptions = {
tags: "".split(" "),
id: "69"
};
initTagRenderer("".split(" "), "".split(" "), channelOptions);
StackExchange.using("externalEditor", function() {
// Have to fire editor after snippets, if snippets enabled
if (StackExchange.settings.snippets.snippetsEnabled) {
StackExchange.using("snippets", function() {
createEditor();
});
}
else {
createEditor();
}
});
function createEditor() {
StackExchange.prepareEditor({
heartbeatType: 'answer',
autoActivateHeartbeat: false,
convertImagesToLinks: true,
noModals: true,
showLowRepImageUploadWarning: true,
reputationToPostImages: 10,
bindNavPrevention: true,
postfix: "",
imageUploader: {
brandingHtml: "Powered by u003ca class="icon-imgur-white" href="https://imgur.com/"u003eu003c/au003e",
contentPolicyHtml: "User contributions licensed under u003ca href="https://creativecommons.org/licenses/by-sa/3.0/"u003ecc by-sa 3.0 with attribution requiredu003c/au003e u003ca href="https://stackoverflow.com/legal/content-policy"u003e(content policy)u003c/au003e",
allowUrls: true
},
noCode: true, onDemand: true,
discardSelector: ".discard-answer"
,immediatelyShowMarkdownHelp:true
});
}
});
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3025277%2ffinds-the-analytical-form-of-the-row-sum-of-the-inverse-of-a-tridiagonal-matrix%23new-answer', 'question_page');
}
);
Post as a guest
Required, but never shown
2 Answers
2
active
oldest
votes
2 Answers
2
active
oldest
votes
active
oldest
votes
active
oldest
votes
$begingroup$
Let $s = (s_i)$ be the $Ntimes 1$ matrix of row sums. i.e. the entry at $i^{th}$ row is $s_i = s(i)$.
Let $u$ be the $Ntimes 1$ matrix with all entries $1$. By definition of the row sums, we have
$$s = A^{-1} u quadiffquad As = u$$
Express everyting in terms of entries of $A$ and $s$, this is equivalent to following set of equations:
$$begin{array}{rrrrrrl}
- 2 s_1& + s_2&&&& = N+1\
s_1 & -2s_2& + s_3 &&& = N+1\
&& ddots & ddots & +s_{N} &= N+1\
&&&s_{N-1}&{ -2s_{N}} &= N+1
end{array}tag{*1}$$
Introduce two dummy variables $s_0 = s_{N+1} = 0$. This can be summarized as
$$s_{k-1} - 2s_{k} + s_{k+1} = N+1quadtext{ for } k = 1,ldots, N$$
Notice what's on the left has the form of second order finite difference. To get a constant
on the right. $s_k$ need to be a quadratic polynomial in $k$.
Since $s_0 = s_{N+1} = 0$, we have $s_{k} = alpha k (k - N - 1)$ for some constant $alpha$. One can fix $a$ using any equation in $(*1)$. At the end, we find $alpha = frac{N+1}{2}$ and
$$s(k) = s_k = frac{N+1}{2}k(k - N - 1)$$
$endgroup$
add a comment |
$begingroup$
Let $s = (s_i)$ be the $Ntimes 1$ matrix of row sums. i.e. the entry at $i^{th}$ row is $s_i = s(i)$.
Let $u$ be the $Ntimes 1$ matrix with all entries $1$. By definition of the row sums, we have
$$s = A^{-1} u quadiffquad As = u$$
Express everyting in terms of entries of $A$ and $s$, this is equivalent to following set of equations:
$$begin{array}{rrrrrrl}
- 2 s_1& + s_2&&&& = N+1\
s_1 & -2s_2& + s_3 &&& = N+1\
&& ddots & ddots & +s_{N} &= N+1\
&&&s_{N-1}&{ -2s_{N}} &= N+1
end{array}tag{*1}$$
Introduce two dummy variables $s_0 = s_{N+1} = 0$. This can be summarized as
$$s_{k-1} - 2s_{k} + s_{k+1} = N+1quadtext{ for } k = 1,ldots, N$$
Notice what's on the left has the form of second order finite difference. To get a constant
on the right. $s_k$ need to be a quadratic polynomial in $k$.
Since $s_0 = s_{N+1} = 0$, we have $s_{k} = alpha k (k - N - 1)$ for some constant $alpha$. One can fix $a$ using any equation in $(*1)$. At the end, we find $alpha = frac{N+1}{2}$ and
$$s(k) = s_k = frac{N+1}{2}k(k - N - 1)$$
$endgroup$
add a comment |
$begingroup$
Let $s = (s_i)$ be the $Ntimes 1$ matrix of row sums. i.e. the entry at $i^{th}$ row is $s_i = s(i)$.
Let $u$ be the $Ntimes 1$ matrix with all entries $1$. By definition of the row sums, we have
$$s = A^{-1} u quadiffquad As = u$$
Express everyting in terms of entries of $A$ and $s$, this is equivalent to following set of equations:
$$begin{array}{rrrrrrl}
- 2 s_1& + s_2&&&& = N+1\
s_1 & -2s_2& + s_3 &&& = N+1\
&& ddots & ddots & +s_{N} &= N+1\
&&&s_{N-1}&{ -2s_{N}} &= N+1
end{array}tag{*1}$$
Introduce two dummy variables $s_0 = s_{N+1} = 0$. This can be summarized as
$$s_{k-1} - 2s_{k} + s_{k+1} = N+1quadtext{ for } k = 1,ldots, N$$
Notice what's on the left has the form of second order finite difference. To get a constant
on the right. $s_k$ need to be a quadratic polynomial in $k$.
Since $s_0 = s_{N+1} = 0$, we have $s_{k} = alpha k (k - N - 1)$ for some constant $alpha$. One can fix $a$ using any equation in $(*1)$. At the end, we find $alpha = frac{N+1}{2}$ and
$$s(k) = s_k = frac{N+1}{2}k(k - N - 1)$$
$endgroup$
Let $s = (s_i)$ be the $Ntimes 1$ matrix of row sums. i.e. the entry at $i^{th}$ row is $s_i = s(i)$.
Let $u$ be the $Ntimes 1$ matrix with all entries $1$. By definition of the row sums, we have
$$s = A^{-1} u quadiffquad As = u$$
Express everyting in terms of entries of $A$ and $s$, this is equivalent to following set of equations:
$$begin{array}{rrrrrrl}
- 2 s_1& + s_2&&&& = N+1\
s_1 & -2s_2& + s_3 &&& = N+1\
&& ddots & ddots & +s_{N} &= N+1\
&&&s_{N-1}&{ -2s_{N}} &= N+1
end{array}tag{*1}$$
Introduce two dummy variables $s_0 = s_{N+1} = 0$. This can be summarized as
$$s_{k-1} - 2s_{k} + s_{k+1} = N+1quadtext{ for } k = 1,ldots, N$$
Notice what's on the left has the form of second order finite difference. To get a constant
on the right. $s_k$ need to be a quadratic polynomial in $k$.
Since $s_0 = s_{N+1} = 0$, we have $s_{k} = alpha k (k - N - 1)$ for some constant $alpha$. One can fix $a$ using any equation in $(*1)$. At the end, we find $alpha = frac{N+1}{2}$ and
$$s(k) = s_k = frac{N+1}{2}k(k - N - 1)$$
edited Dec 4 '18 at 9:42
answered Dec 4 '18 at 9:35
achille huiachille hui
95.7k5132258
95.7k5132258
add a comment |
add a comment |
$begingroup$
The elements of the inverse are
$$
[A^{-1}]_{ij} = (N + 1) begin{cases}
(-1)^{i + j} theta_{i - 1}phi_{j + 1}/theta_N & i < j \
theta_{i - 1}phi_{j + 1}/theta_N & i = j tag{1} \
(-1)^{i + j} theta_{j - 1}phi_{i + 1}/theta_N & i > j \
end{cases}
$$
where $theta$ satisfy the recurrence relation
$$
theta_i = -2theta_{i - 1} - theta_{i - 2}
$$
with initial condition $theta_0 = 1$, $theta_1 = -2$ this leads to
$$
theta_i = (-1)^{i}(i + 1) tag{2}
$$
Similarly
$$
phi_i = -2phi_{i + 1} - phi_{i + 2}
$$
with conditions $phi_{N + 1} = 1$, $phi_N = -2$:
$$
phi_{i} = (-1)^{1 + i - N}(2 - i + N) tag{3}
$$
Replacing in $(1)$, you get
begin{eqnarray}
[A^{-1}]_{ij} &=& (N + 1) begin{cases}
(-1)^{i + j} (-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i < j \
(-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i = j \
(-1)^{i + j} (-1)^{j - 1}j(-1)^{2 + i - N}(1 - i + N)/(-1)^N(N + 1) & i > j \
end{cases} \ &=&
-begin{cases}
i(1 - j + N) & i < j \
i(1 - j + N) & i = j tag{4}\
j(1 - i + N) & i > j \
end{cases}
end{eqnarray}
Now it is a matter of adding these components
$$bbox[5px,border:2px solid blue]
{
s_i = sum_{j = 1}^N [A^{-1}]_{ij} = begin{cases}
N(N - 7)(N + 1)/2 & 1 leq N leq 8 \
4(N^2 - 6N - 7) & text{otherwise}
end{cases}
}
$$
$endgroup$
$begingroup$
$N = 1, 8$ isn't a special case; the formula for $1<N<8$ still applies.
$endgroup$
– Display name
Dec 4 '18 at 9:35
$begingroup$
@Displayname Thanks for the suggestion. Already fixed it
$endgroup$
– caverac
Dec 4 '18 at 9:37
add a comment |
$begingroup$
The elements of the inverse are
$$
[A^{-1}]_{ij} = (N + 1) begin{cases}
(-1)^{i + j} theta_{i - 1}phi_{j + 1}/theta_N & i < j \
theta_{i - 1}phi_{j + 1}/theta_N & i = j tag{1} \
(-1)^{i + j} theta_{j - 1}phi_{i + 1}/theta_N & i > j \
end{cases}
$$
where $theta$ satisfy the recurrence relation
$$
theta_i = -2theta_{i - 1} - theta_{i - 2}
$$
with initial condition $theta_0 = 1$, $theta_1 = -2$ this leads to
$$
theta_i = (-1)^{i}(i + 1) tag{2}
$$
Similarly
$$
phi_i = -2phi_{i + 1} - phi_{i + 2}
$$
with conditions $phi_{N + 1} = 1$, $phi_N = -2$:
$$
phi_{i} = (-1)^{1 + i - N}(2 - i + N) tag{3}
$$
Replacing in $(1)$, you get
begin{eqnarray}
[A^{-1}]_{ij} &=& (N + 1) begin{cases}
(-1)^{i + j} (-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i < j \
(-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i = j \
(-1)^{i + j} (-1)^{j - 1}j(-1)^{2 + i - N}(1 - i + N)/(-1)^N(N + 1) & i > j \
end{cases} \ &=&
-begin{cases}
i(1 - j + N) & i < j \
i(1 - j + N) & i = j tag{4}\
j(1 - i + N) & i > j \
end{cases}
end{eqnarray}
Now it is a matter of adding these components
$$bbox[5px,border:2px solid blue]
{
s_i = sum_{j = 1}^N [A^{-1}]_{ij} = begin{cases}
N(N - 7)(N + 1)/2 & 1 leq N leq 8 \
4(N^2 - 6N - 7) & text{otherwise}
end{cases}
}
$$
$endgroup$
$begingroup$
$N = 1, 8$ isn't a special case; the formula for $1<N<8$ still applies.
$endgroup$
– Display name
Dec 4 '18 at 9:35
$begingroup$
@Displayname Thanks for the suggestion. Already fixed it
$endgroup$
– caverac
Dec 4 '18 at 9:37
add a comment |
$begingroup$
The elements of the inverse are
$$
[A^{-1}]_{ij} = (N + 1) begin{cases}
(-1)^{i + j} theta_{i - 1}phi_{j + 1}/theta_N & i < j \
theta_{i - 1}phi_{j + 1}/theta_N & i = j tag{1} \
(-1)^{i + j} theta_{j - 1}phi_{i + 1}/theta_N & i > j \
end{cases}
$$
where $theta$ satisfy the recurrence relation
$$
theta_i = -2theta_{i - 1} - theta_{i - 2}
$$
with initial condition $theta_0 = 1$, $theta_1 = -2$ this leads to
$$
theta_i = (-1)^{i}(i + 1) tag{2}
$$
Similarly
$$
phi_i = -2phi_{i + 1} - phi_{i + 2}
$$
with conditions $phi_{N + 1} = 1$, $phi_N = -2$:
$$
phi_{i} = (-1)^{1 + i - N}(2 - i + N) tag{3}
$$
Replacing in $(1)$, you get
begin{eqnarray}
[A^{-1}]_{ij} &=& (N + 1) begin{cases}
(-1)^{i + j} (-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i < j \
(-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i = j \
(-1)^{i + j} (-1)^{j - 1}j(-1)^{2 + i - N}(1 - i + N)/(-1)^N(N + 1) & i > j \
end{cases} \ &=&
-begin{cases}
i(1 - j + N) & i < j \
i(1 - j + N) & i = j tag{4}\
j(1 - i + N) & i > j \
end{cases}
end{eqnarray}
Now it is a matter of adding these components
$$bbox[5px,border:2px solid blue]
{
s_i = sum_{j = 1}^N [A^{-1}]_{ij} = begin{cases}
N(N - 7)(N + 1)/2 & 1 leq N leq 8 \
4(N^2 - 6N - 7) & text{otherwise}
end{cases}
}
$$
$endgroup$
The elements of the inverse are
$$
[A^{-1}]_{ij} = (N + 1) begin{cases}
(-1)^{i + j} theta_{i - 1}phi_{j + 1}/theta_N & i < j \
theta_{i - 1}phi_{j + 1}/theta_N & i = j tag{1} \
(-1)^{i + j} theta_{j - 1}phi_{i + 1}/theta_N & i > j \
end{cases}
$$
where $theta$ satisfy the recurrence relation
$$
theta_i = -2theta_{i - 1} - theta_{i - 2}
$$
with initial condition $theta_0 = 1$, $theta_1 = -2$ this leads to
$$
theta_i = (-1)^{i}(i + 1) tag{2}
$$
Similarly
$$
phi_i = -2phi_{i + 1} - phi_{i + 2}
$$
with conditions $phi_{N + 1} = 1$, $phi_N = -2$:
$$
phi_{i} = (-1)^{1 + i - N}(2 - i + N) tag{3}
$$
Replacing in $(1)$, you get
begin{eqnarray}
[A^{-1}]_{ij} &=& (N + 1) begin{cases}
(-1)^{i + j} (-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i < j \
(-1)^{i - 1}i(-1)^{2 + j - N}(1 - j + N)/(-1)^N(N + 1) & i = j \
(-1)^{i + j} (-1)^{j - 1}j(-1)^{2 + i - N}(1 - i + N)/(-1)^N(N + 1) & i > j \
end{cases} \ &=&
-begin{cases}
i(1 - j + N) & i < j \
i(1 - j + N) & i = j tag{4}\
j(1 - i + N) & i > j \
end{cases}
end{eqnarray}
Now it is a matter of adding these components
$$bbox[5px,border:2px solid blue]
{
s_i = sum_{j = 1}^N [A^{-1}]_{ij} = begin{cases}
N(N - 7)(N + 1)/2 & 1 leq N leq 8 \
4(N^2 - 6N - 7) & text{otherwise}
end{cases}
}
$$
edited Dec 4 '18 at 14:51
answered Dec 4 '18 at 9:34
caveraccaverac
14.5k31130
14.5k31130
$begingroup$
$N = 1, 8$ isn't a special case; the formula for $1<N<8$ still applies.
$endgroup$
– Display name
Dec 4 '18 at 9:35
$begingroup$
@Displayname Thanks for the suggestion. Already fixed it
$endgroup$
– caverac
Dec 4 '18 at 9:37
add a comment |
$begingroup$
$N = 1, 8$ isn't a special case; the formula for $1<N<8$ still applies.
$endgroup$
– Display name
Dec 4 '18 at 9:35
$begingroup$
@Displayname Thanks for the suggestion. Already fixed it
$endgroup$
– caverac
Dec 4 '18 at 9:37
$begingroup$
$N = 1, 8$ isn't a special case; the formula for $1<N<8$ still applies.
$endgroup$
– Display name
Dec 4 '18 at 9:35
$begingroup$
$N = 1, 8$ isn't a special case; the formula for $1<N<8$ still applies.
$endgroup$
– Display name
Dec 4 '18 at 9:35
$begingroup$
@Displayname Thanks for the suggestion. Already fixed it
$endgroup$
– caverac
Dec 4 '18 at 9:37
$begingroup$
@Displayname Thanks for the suggestion. Already fixed it
$endgroup$
– caverac
Dec 4 '18 at 9:37
add a comment |
Thanks for contributing an answer to Mathematics Stack Exchange!
- Please be sure to answer the question. Provide details and share your research!
But avoid …
- Asking for help, clarification, or responding to other answers.
- Making statements based on opinion; back them up with references or personal experience.
Use MathJax to format equations. MathJax reference.
To learn more, see our tips on writing great answers.
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
StackExchange.ready(
function () {
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f3025277%2ffinds-the-analytical-form-of-the-row-sum-of-the-inverse-of-a-tridiagonal-matrix%23new-answer', 'question_page');
}
);
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Sign up or log in
StackExchange.ready(function () {
StackExchange.helpers.onClickDraftSave('#login-link');
});
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Sign up using Google
Sign up using Facebook
Sign up using Email and Password
Post as a guest
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown
Required, but never shown